Digital Signal Processing Approach for Modeling Electrically and Magnetically Dispersive Electromagnetic Applications - Ramadan, Omar (IEEE, 2013)
In this paper, digital signal processing (DSP) approach is developed for solving electrically and magnetically dispersive electromagnetic applications in the discrete time domain. This approach is based on incorporating the DSP algorithms developed for digital filters into the finite difference time domain (FDTD) method. In the proposed approach, the dielectric parameters of each FDTD grid point is interpreted as an infinite impulse response digital filter, which can be implemented in the discrete time efficiently using the transpose direct form II. Numerical example carried out for negative index meta-materials (NIMs) is included to show the validity of the proposed formulation.
IEEE Jordan Conference on Applied Electrical Engineering and Computing Technologies (AEECT) -- DEC 03-05, 2013 -- Univ Jordan, Fac Engn & Technol, Amman, JORDAN
Keywords: Digital signal processing; digital filter; finite difference time domain; infinite impulse response; electrically and magnetically dispersive materials